2010
DOI: 10.1016/j.cherd.2009.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Reducing energy consumption and CO2 emissions in extractive distillation: Part II. Dynamic behavior

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues.Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. b s t r a c tThe structure of thermally coupled distillation systems offers several control challenges arising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 36 publications
3
13
0
Order By: Relevance
“…In this case a sufficiently complete range of frequencies was covered. Similar studies have been reported by Jantes-Jaramillo et al [23], Gómez-Castro et al [18,24], and Ibarra-Sánchez and Segovia-Hernández [25] among others, for the control analysis of complex distillation systems. Other techniques available for the dynamic analysis of distillation systems are the relative gain array (RGA) analysis and the Niederlinski Index (NI) analysis, which allows to determinate the best pairing alternatives between control loops [26].…”
Section: Singular Value Decomposition Technique (Svd)supporting
confidence: 67%
“…In this case a sufficiently complete range of frequencies was covered. Similar studies have been reported by Jantes-Jaramillo et al [23], Gómez-Castro et al [18,24], and Ibarra-Sánchez and Segovia-Hernández [25] among others, for the control analysis of complex distillation systems. Other techniques available for the dynamic analysis of distillation systems are the relative gain array (RGA) analysis and the Niederlinski Index (NI) analysis, which allows to determinate the best pairing alternatives between control loops [26].…”
Section: Singular Value Decomposition Technique (Svd)supporting
confidence: 67%
“…The overall behavior of the plant has also been utilized instead of a quantitative model to design a controller [26]. In short, a variety of solutions have been investigated and applied to counter the challenges posed by high-purity distillation columns [41][42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…Azeotropic and close boiling components are commonly encountered in fine‐chemical and specialty industries. The separation of these mixtures is a challenging task in many chemical processes, which is impossible using a single conventional distillation column, and many nonconventional distillation techniques have been proposed to solve this problem . The most common alternatives involve changing the operating pressure or adding a separation solvent.…”
Section: Introductionmentioning
confidence: 99%